TOWARDS EXTENDING THE ORIGINAL TECHNOLOGY ACCEPTANCE MODEL (TAM) FOR A BETTER UNDERSTANDING OF EDUCATIONAL TECHNOLOGY ADOPTION - Sukackė, Vilma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Technology acceptance model (TAM) is arguably the most widely used intention theory that explains the individual’s acceptance of a certain technology. Since Davis introduced TAM in 1986, it has been applied and validated in a variety of disciplines, including educational sciences. However, scholars note that depending on a specific context, the original TAM needs to be extended, which has been done by introducing external variables and other theories. Despite the existent TAM2 and TAM3, numerous scholars still opt for the original TAM, extending it with the variables and theories that are relevant to the specific context of their study. The aim of the present paper is to provide an overview of validated TAM extensions, which might later help to further the understanding of educational technology acceptance, which is a prerequisite of its adoption. Since interdisciplinarity in various contexts is becoming more and more common, the overview presents TAM extensions that come from a number of different disciplines. The overview is based on 108 papers that were retrieved from the Web of Science (Clarivate Analytics) by searching for the keywords ‘extended Technology Acceptance Model’, ‘extended TAM’, and ‘TAM extension’.